1990
DOI: 10.1093/ije/19.3.698
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Passive Measles Antibody in Jamaican Children

Abstract: Measles antibody titres were determined by haemagglutination inhibition and by neutralization in 221 sets of serum collected from delivering mothers, umbilical cords, and infants when about six months of age. Radio-immunoassay was also used to measure antibody in 120 sera. Total IgG concentration was determined in the infant sera. All mothers had measles antibody and the mean titre was high. At the time of birth, measles antibody had been further concentrated in the infant. Nevertheless, many children lost pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our data suggest that almost onefifth (17.6% [95% CI, 9.6%-25.6%) of children born to HIVinfected mothers are seronegative for measles antibodies at birth. Although the present study did not assess levels of maternal measles antibodies during infancy, previous studies have reported that infants born with low levels of maternal measles antibodies continue to have lower levels over time, compared with those who are born with higher levels [39,40]. Furthermore, a proportion of adults in this rural area are seronegative for measles antibodies.…”
Section: Discussionmentioning
confidence: 78%
“…Our data suggest that almost onefifth (17.6% [95% CI, 9.6%-25.6%) of children born to HIVinfected mothers are seronegative for measles antibodies at birth. Although the present study did not assess levels of maternal measles antibodies during infancy, previous studies have reported that infants born with low levels of maternal measles antibodies continue to have lower levels over time, compared with those who are born with higher levels [39,40]. Furthermore, a proportion of adults in this rural area are seronegative for measles antibodies.…”
Section: Discussionmentioning
confidence: 78%
“…Maternal antibodies are the major immune mechanism that protects neonates against pathogens, but they can also interfere with the effects of immunization 22 , 23 . The weakened rate in neonates was different in different regions because of the different levels of infection rates and titers.…”
Section: Discussionmentioning
confidence: 99%
“…Ochola et al demonstrated the half-life of passively acquired maternal RSV antibodies in infants was 79 days. [50] Other studies of the persistence of passive maternal antibodies to H.pylori and measles both suggest that immunity has waned by 6 months after birth [48], [49], [51]; however other work suggests the half-life period for influenza antibodies may vary. [52][54] …”
Section: Discussionmentioning
confidence: 99%